MENINGKATKAN HASIL BELAJAR IPA MELALUI MEDIA INTERAKTIF DENGAN MENGGUNAKAN PERMAINAN PUZZLE - Mufathika, Ruchana; Setyawan, Danang Budi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The research objectives were to determine' enthusiasm for learning and student learning outcomes after applying the puzzle game to students at Muhammadiyah 7 Bayat Middle School on Human Excretory System Material. The research method uses Classroom Action Research (PTK), with procedures: planning, action, observation and reflection. The research subjects were teachers and students of class VIII B. Data collection techniques used observation sheets and reflection sheets. Data analysis uses qualitative descriptive statistics. The results of the research conclude: (1) The application of interactive learning media using puzzle games is able to increase students' enthusiasm for learning during learning. Students hold discussions or exchange ideas, and students also look happy and enthusiastic about learning. Learning tends to be student-centered, and teachers play more of a role as motivators and facilitators; (2) The application of interactive learning media using puzzle games can improve student learning outcomes and learning completeness. This is because this learning model can make it easier for students to understand the subject matter. Student learning completeness in the pre-cycle was 5 students (18%), then in cycle I it increased to 18 students (64%), and in cycle II it increased again to 24 students (86%).